Education, disadvantage and place : making the local matter - Kerr, Kirstin; Dyson, Alan; Raffo, Carlo (Policy Press, 2014)
Challenging current thinking, this important book is the first to focus on the role of area-based initiatives to tackle the link between education, disadvantage and place. Aimed at all those actively seeking to tackle disadvantage, including policymakers, practitioners, academics and students.